The Third International Symposium on Fungal Stress – ISFUS. Issue 5 (May 2020) - Alder-Rangel, Alene; Idnurm, Alexander; Brand, Alexandra C.; Brown, Alistair J.P.; Gorbushina, Anna; Kelliher, Christina M.; Campos, Claudia B.; Levin, David E.; Bell-Pedersen, Deborah; Dadachova, Ekaterina; Bauer, Florian F.; Gadd, Geoffrey M.; et al.
Abstract: Stress is a normal part of life for fungi, which can survive in environments considered inhospitable or hostile for other organisms. Due to the ability of fungi to respond to, survive in, and transform the environment, even under severe stresses, many researchers are exploring the mechanisms that enable fungi to adapt to stress. The International Symposium on Fungal Stress (ISFUS) brings together leading scientists from around the world who research fungal stress. This article discusses presentations given at the third ISFUS, held in São José dos Campos, São Paulo, Brazil in 2019, thereby summarizing the state-of-the-art knowledge on fungal stress, a field that includes microbiology, agriculture, ecology, biotechnology, medicine, and astrobiology. Graphical abstract: Image 1